Defining 'Housing Developer' and 'Housing Development' under Malaysian Housing Law - Md Dahlan, Nuarrual Hilal; Kamaruddin, Abdul Rani (Universiti Utara Malaysia Press, 2010)
The words ‘housing developer’ and ‘housing development’ have been defined in section 3 of the Housing Development (Control and Licensing) Act 1966 (‘the Act’). These statutory definitions have severally been discussed and examined by the courts in several case law and it has been contended that the meanings of the definitions are too loose,enigmatic and vague. The certitude on the meaning of ‘housing developer’ and ‘housing development’ is a must for otherwise, it would be difficult for the Ministry of Housing and Local Government (MHLG) and as well as to the public to identify persons deemed to be ‘housing developers’ or carrying out ‘housing development’. It is perceived that not all persons, who have literally been called as ‘housing developers’, or carrying out ‘housing developments’ activities fall within the intended legal and statutory definitions of the Act. Thus they are not required to abide by the provisions of the Act. Conversely, persons who may have been initially deemed not to have undertaken activities of ‘housing developer’ or carrying out ‘housing development’, yet based on the principles adopted and defined in section 3 of the Act and the judgments in the case law, have rendered them not to have fallen into the meaning of ‘housing developers’ and/or carrying out ‘housing development’ and thus are subject to the provisions and obligations provided in the Act. Again, based on examinations over these definitions, it is found that the definitions of ‘housing developer’ and ‘housing development’ as spelt out in section 3 and surprisingly from the principles enunciated in the case law, the meaning of ‘housing developer’ and ‘housing development’ are still uncertain and open to various interpretations.